PRAGMATIC FUNCTIONS OF PROVERBS IN ENGLISH AND UZBEK LANGUAGES - Nuriddinova Khuriyat (The Conference Hub, 2025)
This article examines the pragmatic functions of proverbs in English and Uzbek languages through a comparative analysis. Proverbs are studied not only as stylistic devices but also as communicative tools that serve specific pragmatic purposes. The research identifies the main functions of proverbs, including didactic, persuasive, warning, evaluative, and aesthetic roles. The findings reveal that while English and Uzbek proverbs share similar pragmatic functions, their symbolic imagery reflects distinct cultural backgrounds. For instance, Uzbek proverbs often draw on agricultural life, family values, and collectivist traditions, whereas English proverbs tend to emphasize individualism, maritime experience, and pragmatic reasoning. The study concludes that analyzing the pragmatic functions of proverbs provides deeper insight into national worldviews and cultural values, as well as offering theoretical support for more accurate translation and intercultural communication.
Keywords: proverb, pragmatics, English, Uzbek, communicative function, culture, comparative analysis.